Patient satisfaction and perception of quality care in orthodontic services using the servqual model at a tertiary care hospital - Zahra Masood; Fizzah Ikram; Mubassar Fida; Rashna Hoshang Sukhia (Journal of the Pakistan Medical Association, 2026)
Objective: To assess patient satisfaction and the perceived quality of orthodontic care in a tertiary care setting, focussing on identifying gaps between patients’ expectations and perceptions. Method: The cross-sectional study was conducted at the Department of Orthodontics, Aga Khan University Hospital, Karachi, in January 2025, and comprised orthodontic patients undergoing treatment for at least six months. Data was collected using a structured SERVQUAL-based questionnaire which was distributed online. The primary outcome was the difference between expectation and perception scores for each SERVQUAL dimension of tangibles, reliability, responsiveness, assurance and empathy. Data was analysed using SPSS for windows (version 23.0, SPSS Inc, Chicago) Results: Of the 58 patients, 41(70.7%) were females with mean age 24.2±5.5 years and 17(29.3%) were males with mean age 22.4±12.2 years. A significant gap was observed between patients’ expectations and perceptions in reliability and empathy dimensions (p<0.05). Conversely, the highest perception scores were noted in assurance and responsiveness dimensions (p<0.05). Conclusions: There were significant gaps between patients’ expectations and perceptions with respect to reliability and empathy, while high satisfaction levels were noted for assurance and responsiveness. Key Words: Patient satisfaction, Service quality, Orthodontic care, SERVQUAL model